In situ assembly of Ag nanoparticles (AgNPs) on porous silkworm cocoon-based wound film: enhanced antimicrobial and wound healing activity - Kun Yu (Nature Portfolio, 2017)
Abstract Preventing wound infection and retaining an appropriate level of moisture around wounds represent the most critical issues in wound treatment. Towards these ends, special focus has been placed on Bombyx mori cocoons because the protective function of the silkworm cocoon resembles the manner in which the skin protects the human body. We have designed a facile technique to develop a novel silkworm cocoon-based wound film (SCWF) wound dressing utilizing a CaCl2-ethanol-H2O solution. To improve the anti-bacterial performance of SCWF, we have incorporated the ability of silk sericin to act as a reducing agent for the conversion of Ag+ to Ag, yielding nanoparticles (AgNPs) linked together by peptide bonds of silkworm cocoon wound film (SCWF-AgNPs). SCWF-AgNP dressing exhibited excellent biocompatibility, anti-bacterial performance, and good extensibility. Furthermore, in vivo experiments indicated that SCWF-AgNP dressing was able to significantly accelerate the healing rate of infected wounds in New Zealand White rabbits and histological examination revealed that it aided in the successful reconstruction of intact and thickened epidermis during 14 days of healing of impaired wound tissue. These results demonstrate that the present approach might shed new light on the design of anti-bacterial materials such as SCWF-AgNPs with promising applications in wound dressing.